Effects of short-term training on physiologic properties of human motor units - Doherty, T. J. (Canadian Journal of Applied Physiology, 2000)
The human neuromuscular system possesses a remarkable ability to adapt to any change in the demands placed upon it. Adaptation to training or disuse is reflected in the activation patterns and physiologic properties of the motor unit (MU) pool in a given muscle group. This review summarizes the studies that have examined such adaptation at the level of the single MU. Disuse, as revealed by electrophysiologic studies, results in impaired MU recruitment and smaller twitch tensions in low and high threshold MUs. Alternatively, short-term training improves MU recruitment and generally results in larger MU twitch tensions. A method has been developed to physiologically characterize and longitudinally follow single thenar MUs. Studies utilizing these methods have demonstrated that MUs differing in their baseline physiologic characteristics respond very differently to identical short-term training programs. These observations at the single MU level provide insight into training adaptations in whole muscles and muscle groups.